A note on the simplex-cosimplex problem. (December 2017) - Adiprasito, Karim
Abstract: We construct, for every dimension d ≥ 3, polytopal spheres S for which neither S nor its dual S ∗ contain 2-faces that are triangles. This answers the topological formulation of a problem of Kalai, Kleinschmidt and Meisinger.